Meldonium Inhibits Cell Motility and Wound-Healing in Trabecular Meshwork Cells and Scleral Fibroblasts: Possible Applications in Glaucoma - Cristina Minnelli; Francesco Piva; Monia Cecati; Tatiana Armeni; Giovanna Mobbili; Roberta Galeazzi; Alberto Melecchi; Martina Cristaldi; Roberta Corsaro; Dario Rusciano (Pharmaceuticals, 2023)
Meldonium (MID) is a synthetic drug designed to decrease the availability of L-carnitine—a main player in mitochondrial energy generation—thus modulating the cell pathways of energy metabolism. Its clinical effects are mostly evident in blood vessels during ischemic events, when the hyperproduction of endogenous carnitine enhances cell metabolic activities, leading to increased oxidative stress and apoptosis. MID has shown vaso-protective effects in model systems of endothelial dysfunction induced by high glucose or by hypertension. By stimulating the endothelial nitric oxide synthetase (eNOS) via PI3 and Akt kinase, it has shown beneficial effects on the microcirculation and blood perfusion. Elevated intraocular pressure (IOP) and endothelial dysfunction are major risk factors for glaucoma development and progression, and IOP remains the main target for its pharmacological treatment. IOP is maintained through the filtration efficiency of the trabecular meshwork (TM), a porous tissue derived from the neuroectoderm. Therefore, given the effects of MID on blood vessels and endothelial cells, we investigated the effects of the topical instillation of MID eye drops on the IOP of normotensive rats and on the cell metabolism and motility of human TM cells in vitro. Results show a significant dose-dependent decrease in the IOP upon topic treatment and a decrease in TM cell motility in the wound-healing assay, correlating with an enhanced expression of vinculin localized in focal adhesion plaques. Motility inhibition was also evident on scleral fibroblasts in vitro. These results may encourage a further exploration of MID eye drops in glaucoma treatment.